Dari Inovasi ke Penghentian (Analisis Adopsi Inovasi Presenter Artificial Intelligence (AI) di tvOne) - Ikhwan, Muhammad; Prihatmadi, Sekarseta (Fakultas Ilmu Komunikasi UKWMS, 2025)
Media companies, lately, increasingly use artificial intelligence (AI) in news production. an example is the use of AI presenters on tvOne. This study wants to see how the adoption of AI presenters on tvOne. The analysis of research findings uses the theory of innovation diffusion, especially the innovation-decision process model, namely from the stages of knowledge, persuasion, decision, implementation, and confirmation. The Technology Acceptance Model (TAM) theory is also used as a supporting theory. This study uses a case study method, through observation, in-depth interviews, and literature studies. The results, the innovation decision process can be seen in the characteristics of the innovator's values and the influence of socio-economic values. At the persuasion stage, innovators and users are aware of the importance of eradicating deepfakes. From a psychological perspective, the use of AI presenters is based on the desire of tvOne management to make their media a leader in the use of AI technology. At the decision stage, it is realized by showing AI presenters on TV screens, news portals, and 3 social media platforms. At the implementation stage, AI presenters encounter several obstacles. Such as production speed factors that cannot be met, the difficulty of coordination between providers and users of AI presenters, and low audience acceptance. So at the confirmation stage, the AI presenter was finally stopped or discontinued. From the TAM theory, the decision to adopt an AI presenter is based on the aspects of Intention to Use, Usage Behavior, Perceived Usefulness, and Perceived Ease of Use. ABSTRAK Perusahaan media, akhir akhir semakin banyak menggunakan kecerdasan buatan (AI) dalam produksi berita. Salah satunya pemanfaatan presenter AI di TvOne. Penelitian ini ingin melihat bagaimana adopsi presenter AI di tvOne. Analisis temuan penelitian menggunakan teori difusi inovasi, khususnya model inovation-decision procces, yakni dari tahapan pengetahuan, persuasi, keputusan, implementasi dan konfirmasi. Teori Technology Acceptance Model (TAM) juga digunakan sebagai teori pendukung. Penelitian ini menggunakan metode studi kasus, melalui observasi, wawancara mendalam, dan studi pustaka. Hasilnya, dari sisi pengetahuan, proses keputusan inovasi terlihat pada karakteristik nilai pribadi inovator dan pengaruh dari nilai sosial ekonomi. Pada tahapan persuasi, invator dan pengguna (manajemen tvOne) memiliki kesadaran tentang pentingnya memberantas deepfake (berita palsu). Dari sisi keuntungan relatif produksi presenter AI bisa menekan biaya produksi berita. Dari sisi psikologis, pengguaan presenter AI didasarkan atas keinginan manajemen tvone untuk menjadikan medianya sebagai pemimpin (pionir) dalam pemanfaatan teknologi AI. Pada tahapan keputusan diwujudkan dengan penayangan presenter AI di layar TV, portal berita, dan 3 platform media sosial. Pada tahap implementasi, presenter AI menemui beberapa kendala. Seperti faktor kecepatan produksi yang tidak bisa dipenuhi, sulitnya koordinasi antara penyedia dengan pengguna presenter AI, dan rendahnya penerimaan khalayak. Maka pada tahap konfirmasi, presenter AI di tvone akhirnya dihentikan atau discontinuance. Dari sisi teori TAM, keputusan adopsi presenter AI didasarkan atas aspek Intention to Use, Usage Behaviour, Perceived Usefulness, dan Perceived Ease of Use.